On appropriate Finite Element discretization in simulation of gas-based hot sheet metal forming processes. Issue 1 (June 2021) - Baru, N. K.; Teeuwen, T.; Teller, M.; Hojda, S.; Braun, A.; Hirt, G.
Abstract: Gaseous medium is being used for sheet metal forming at elevated temperatures, especially for lightweighting purposes. These processes enable forming of high strength alloys of a wide range of thickness due to low material flow stress as well as improved formability. In these processes, the resulting component properties are an interplay of numerous parameters. Instead of cost and time intensive experiments, FEM aids an effective and economic process optimization and enables a better understanding of the influence of process parameters on the component properties. In the current study, the importance of appropriate discretization of the workpiece within a gas-based hot sheet metal forming process is investigated based on a laboratory scale component. AA6010 sheet metal blanks of different thicknesses are studied numerically and experimentally. Simulations with different types of elements are performed and the evolution of process parameters as well as their influence on the final component thickness are analysed. Different element types resulted in noticeable difference in the simulation results and this difference also varies with the initial sheet thickness. Upon further experimental validation, the suitable element type for workpiece discretization is suggested, which enables practitioners to get reliable results via FE simulation of these processes.